Complete mitochondrial genome of Costaria costata shows conservative evolution in Laminariales. (2nd November 2015) - Qu, Jie-Qiong; Liu, Cui; Wang, Xu-Min; Zhang, Zhao-Bao; Chi, Shan; Liu, Tao
Abstract: Costaria costata, with great commercial and industrial value, typically grows in low intertidal and subtidal retgions in East Asia. The complete mitochondrial genome of C. costata is determined as circular-mapping and AT-rich (65%). The 37, 461 bp mitochondrial genome consists of 25 tRNAs, 38 genes (including ORFs) and 3 ribosome genes. The gene arrangement and component are identical to those of Laminaria mitochondrial genomes, which show highly conservative evolution in mitochondrial genomes within the Laminariales. Moreover, the C. costata mitogenome makes full use of nucleotide and genetic information by large amounts of gene overlappings for better adapting the evolution of small genomes.